Ovine epididymal spermatozoa preservation in liquid state with or without seminal plasma epididimarios ovinos - Bergstein-Galan, Tacia Comes; Weiss, Romildo Romualdo; Rodrigues Barbosa, Thiago Salvati; Kozicki, Luiz Ernandes; Bicudo, Sony Dimas [UNESP] (Univ Federal Santa Maria, 2018)
Preservation and use of spermatozoa that have been recovered after death can extend the use of genetically superior animals. The objective of this study was to evaluate the maximum period for which ovine spermatozoa could be successfully stored in refrigerated dilution medium post-mortem, with or without added seminal plasma. Three samples of spermatozoa collected in an artificial vagina from 10 rams, or from the tails of four epididymes from the same rams at the time of death (G0) and six (G6), twelve (G12), twenty-four (G24) and fortyeight (G48) hours after death were used. After recovery, the spermatozoa were refrigerated at 5 degrees C in either control medium (CM) or control medium plus 20% homologous seminal plasma (SP) and evaluated for 72 hours from the start of refrigeration. The G48 samples had a lower(P < 0.05) total motility (TM) and plasma membrane integrity in the hyposmotic test (HOST) than the other groups evaluated at all analyzed times. The TM decreased (P < 0.05) after 24 hours of cooling in semen collected in AV, at G0 and G24 and after 48 hours of refrigeration in G6 and G12. The TM and HOST integrity and sperm morphology did not differ between samples refrigerated in CM or SP. In conclusion, it is possible to collect epididymal spermatozoa up to 24 hours after death. Sperm viability can be prolonged fora further 48 hours by refrigeration. However, total motility decreases from 24 hours after refrigeration and the supplementation of 20% seminal plasma to the extender has no effect on spermatozoa longevity.
Keywords: refrigeration; epididymis; post mortem